AXL expression reflects tumor-immune cell dynamics impacting outcome in non-small cell lung cancer patients treated with immune checkpoint inhibitor monotherapy - Rayford, Austin; Gärtner, Fabian; Ramnefjell, Maria P.; Lorens, James B.; Micklem, David R.; Aanerud, Marianne; Engelsen, Agnete S. T. (Frontiers in Immunology, 2024)
Introduction AXL receptor expression is proposed to confer immune-checkpoint inhibitor (ICI)-resistance in non-small cell lung cancer (NSCLC) patients. We sought to interrogate AXL expression in conjunction with mutational and tumor-microenvironmental features to uncover predictive mechanisms of resistance in ICI-treated NSCLC patients. Methods Tumor samples from 111 NSCLC patients treated with ICI-monotherapy were analyzed by immunohistochemistry for tumor- and immune-AXL expression. Subsets of patients were analyzed by whole-exome sequencing (n = 44) and imaging mass cytometry (n = 14). Results were related to ICI-outcome measurements. Results Tumor-cell AXL expression correlated with aggressive phenotypic features including reduced OS in patients treated with ICIs (P = 0.04) after chemotherapy progression, but conversely associated with improved disease control (P = 0.045) in ICI-treated, PD-L1 high first-line patients. AXL+ immune-cell infiltration correlated with total immune-cell infiltration and improved overall outcomes (PFS: P = 0.044, OS: P = 0.054). Tumor-cell AXL-upregulation showed enrichment in mutations associated with PD-L1-upregulation and ICI-response such as MUC4 and ZNF469, as well as adverse mutations including CSMD1 and LRP1B which associated with an immune-suppressed tumor phenotype and poor ICI prognosis particularly within chemotherapy-treated patients. Tumor mutational burden had no effect on ICI-outcomes and was associated with a lack of tumor-infiltrating immune cells. Spatial-immunophenotyping provided evidence that tumor-cell AXL-upregulation and adverse mutations modulate the tumor microenvironment in favor of infiltrating, activated neutrophils over anti-tumor immune-subsets including CD4 and CD8 T-cells. Conclusion Tumor-cell AXL-upregulation correlated with distinct oncotypes and microenvironmental immune-profiles that define chemotherapy-induced mechanisms of ICI-resistance, which suggests the combination of AXL inhibitors with current chemoimmunotherapy regimens can benefit NSCLC patients.